HPV16 and 18 genome amplification show different E4-dependence, with 16E4 enhancing E1 nuclear accumulation and replicative efficiency via its cell cycle arrest and kinase activation functions. - Nagayasu Egawa; Qian Wang; Heather M Griffin; Isao Murakami; Deborah Jackson; Radma Mahmood; John Doorbar (PLoS Pathogens)
To clarify E1^E4's role during high-risk HPV infection, the E4 proteins of HPV16 and 18 were compared side by side using an isogenic keratinocyte differentiation model. While no effect on cell proliferation or viral genome copy number was observed during the early phase of either virus life cycle, time-course experiments showed that viral genome amplification and L1 expression were differently affected upon differentiation, with HPV16 showing a much clearer E4 dependency. Although E4 loss never completely abolished genome amplification, its more obvious contribution in HPV16 focused our efforts on 16E4. As previously suggested, in the context of the virus life cycle, 16E4s G2-arrest capability was found to contribute to both genome amplification success and L1 accumulation. Loss of 16E4 also lead to a reduced maintenance of ERK, JNK and p38MAPK activity throughout the genome amplifying cell layers, with 16E4 (but not 18E4) co-localizing precisely with activated cytoplasmic JNK in both wild type raft tissue, and HPV16-induced patient biopsy tissue. When 16E1 was co-expressed with E4, as occurs during genome amplification in vivo, the E1 replication helicase accumulated preferentially in the nucleus, and in transient replication assays, E4 stimulated viral genome amplification. Interestingly, a 16E1 mutant deficient in its regulatory phosphorylation sites no longer accumulated in the nucleus following E4 co-expression. E4-mediated stabilisation of 16E2 was also apparent, with E2 levels declining in organotypic raft culture when 16E4 was absent. These results suggest that 16E4-mediated enhancement of genome amplification involves its cell cycle inhibition and cellular kinase activation functions, with E4 modifying the activity and function of viral replication proteins including E1. These activities of 16E4, and the different kinase patterns seen here with HPV18, 31 and 45, may reflect natural differences in the biology and tropisms of these viruses, as well as differences in E4 function.